SMART TELECOMMUNICATION TECHNOLOGIES FOR MONITORING AND OPERATIONAL INFORMATION SYSTEMS - FABRYKATOR, MYKYTA; YAHANOV, PETRO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper presents the results of research on the use of artificial intelligence technologies in telecommunication systems for monitoring territories and promptly informing the population living in these territories. Such systems are created as hardware and software complexes in which the hardware platform operates under the control of software, interacting with the information space and automating the process of collecting, processing data and making decisions. Modern monitoring and information systems use artificial intelligence technologies, in particular, neural network technologies, which are trained to analyse text messages, identifying semantic entities in them, and combining them by content or location. One of the smart telecommunications technologies that is dynamically developing and constantly improving thanks to new research and development is parsing. Parsing is the process of extracting information from data, whether it is text, code or other structured formats. This is done with the help of algorithms that are able to understand the grammar, syntax, and semantics of the data. The ability to understand is a key characteristic of artificial intelligence, and it is necessary for effective parsing. With the development of artificial intelligence and machine learning, parsing will become an even more powerful and flexible tool, opening up new opportunities for its application in telecommunications. Parsing capabilities are used in this paper to develop and implement an information space monitoring and danger warning system. The paper presents a technical solution of a device based on a microcontroller and a web server that provides access to the information space, acting as a personal danger alert. Regular requests to the web resource and checking the connection status allow timely response to changes, maintaining the relevance and reliability of information for the user